2009
DOI: 10.1103/physrevb.80.205201
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric nature and real-space observations of domain motions in the organic charge-transfer compound tetrathiafulvalene-p-chloranil

Abstract: Ferroelectricity in an organic charge-transfer compound, tetrathiafulvalene-p-chloranil ͑TTF-CA͒, originating from the one-dimensional valence and lattice instabilities, has been investigated by an electroreflectance ͑ER͒ method. Microscopic ER spectroscopy in the visible region enables real-space observations of both ferroelectric domain structures with a few hundred micrometers in size and depinning of the domain walls under strong electric fields. In addition, from ER spectroscopy in the infrared molecular-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…This unusual behavior is emphasized in the vicinity of the NIT and consistent with the findings of electroreflectance spectroscopy 45 as well as theoretical studies: 47 both the ionicity μ and intermolecular covalency within the DA dimer increase with the degree of dimerization (and also with the strength of the applied electric field).…”
Section: Structural Assessments Of the Polarizationsupporting
confidence: 71%
See 1 more Smart Citation
“…This unusual behavior is emphasized in the vicinity of the NIT and consistent with the findings of electroreflectance spectroscopy 45 as well as theoretical studies: 47 both the ionicity μ and intermolecular covalency within the DA dimer increase with the degree of dimerization (and also with the strength of the applied electric field).…”
Section: Structural Assessments Of the Polarizationsupporting
confidence: 71%
“…10 8 ³ cm, even at low temperatures around T c ). 44 As evidence of the ferroelectricity on a mesoscopic scale, Kishida et al 45 found coexisting domains of different polarities in TTFCA through microscopic electro-reflectance spectroscopy. The bulk ferroelectric polarization of TTFQBrCl 3 was later evaluated, which showed better insulating properties (ca.…”
Section: Ferroelectric Propertiesmentioning
confidence: 99%
“…It is worth recalling the discussion of the neutral-ionic transition in TTF-CA, where the increase of the dielectric constant is associated with domain walls [38]. The domains extend over a few hundred micrometers [39].…”
Section: Discussionmentioning
confidence: 99%
“…THz-field-induced changes in the reflectivity of these probe pulses and the SHG intensity were measured using a boxcar integrator. The diameter of the probe pulse was B200 mm, which is comparable to or smaller than the typical size of ferroelectric domains in TTF-CA 15 . Therefore, by selecting an appropriate measured area on a single crystal, the dynamics of a single ferroelectric domain could be detected.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the dimeric molecular displacements are three-dimensionally ordered in phase 13 , yielding in ferroelectricity 14,15 .…”
mentioning
confidence: 99%